A Longitudinal Study of Health Care Resources, Family Support, and Mental Health Outcomes Among Suicidal Adolescents. Issue 1 (6th November 2017) - LeCloux, Mary; Maramaldi, Peter; Thomas, Kristie A.; Maramaldi, Peter; Thomas, Kristie A.; Wharff, Elizabeth A.
Abstract: To inform current public policy regarding suicide prevention, this study examined the longitudinal relationships between four resources (public insurance, primary care services, school‐based mental health treatment, and family support) and depression and suicidality in a nationally representative sample of suicidal adolescents ( n = 1, 355). Longitudinal regression analyses were conducted using data from three waves of the National Longitudinal Study of Adolescent to Adult Health (Add Health). Parental support at Wave I was predictive of lower levels of depression across all three waves, but not significantly associated with the suicide‐specific outcomes. While type of insurance was not significantly associated with any of the outcomes, receipt of public assistance was associated with a higher likelihood of suicidal ideation and higher levels of depression at all three waves. Neither receipt of a routine physical nor access to school‐based mental health treatment were associated with any of the outcomes. Intervention points for future policy that are discussed include the following: integrating family interventions into current screening and referral protocols, targeted screening and outreach for those youth and young adults receiving public assistance, the inclusion of integrated behavioral health in primary care settings, and the inclusion of suicide‐specific evidence‐based treatments in the school setting.